2019
DOI: 10.1111/cbdd.13458
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of novel purine nucleosides bearing a chiral benzoxazine fragment

Abstract: A series of ribo‐ and deoxyribonucleosides bearing 2‐aminopurine as a nucleobase with 7,8‐difluoro‐ 3,4‐dihydro‐3‐methyl‐2H‐[1,4]benzoxazine (conjugated directly or through an aminohexanoyl spacer) was synthesized using an enzymatic transglycosylation reaction. Nucleosides 3‐6 were resistant to deamination under action of adenosine deaminase (ADA) Escherichia coli and ADA from calf intestine. The antiviral activity of the modified nucleosides was evaluated against herpes simplex virus type 1 (HSV‐1, strain L2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…Employing these enzymes, pentose‐1‐phosphates can be obtained as important synthetic intermediates from the accessible pool of nucleosides which have been shown to be highly valuable precursors for the synthesis of base‐ and sugar‐modified nucleosides . Furthermore, NPases are widely used for the synthesis of nucleoside analogues in transglycosylation reactions …”
Section: Introductionmentioning
confidence: 99%
“…Employing these enzymes, pentose‐1‐phosphates can be obtained as important synthetic intermediates from the accessible pool of nucleosides which have been shown to be highly valuable precursors for the synthesis of base‐ and sugar‐modified nucleosides . Furthermore, NPases are widely used for the synthesis of nucleoside analogues in transglycosylation reactions …”
Section: Introductionmentioning
confidence: 99%
“…Nucleoside phosphorylases (NPs), for instance, catalyze the reversible phosphorolytic cleavage of nucleosides into the corresponding free nucleobase and pentose-1-phosphate (Scheme 1) and are widely applied for the preparation of modified nucleosides. [1][2][3][4][5][6][7][8][9][10][11] Consequently, their kinetic and thermodynamic characterization has attracted increased interest and demanded the development of efficient analytical tools. [12,13] Recently, we reported a UV/Vis spectroscopy-based method for the monitoring of these reactions that largely eliminated the need for HPLC.…”
mentioning
confidence: 99%
“…( S )‐ 9b [ α ] D 20 = +105 ( c = 0.85, DMF)]; RP‐HPLC [( S , S )‐Whelk‐O 1, eluent MeOH–0.25 % AcOH 63:27]: t ( R )‐ 9b 11.6 min {ref. : t ( S )‐ 9b 9.0 min}; 97 % ee . 1 H NMR (500 MHz, [D 6 ]DMSO, 100 °C): δ = 1.00 (d, J = 6.7 Hz, 3 H, Me), 1.22–1.30 (m, 2 H, CH 2 hexanoyl), 1.45–1.57 (m, 4 H, CH 2 ‐CH 2 hexanoyl), 2.22 (dt, J = 15.1 and 7.5 Hz, 1 H, 2‐H B hexanoyl), 2.39 (ddd, J = 15.1, 8.2, and 6.6 Hz, 1 H, 2‐H A hexanoyl), 2.77 (dd, J = 12.3 and 4.6 Hz, 1 H, 2‐H B benzothiazine), 3.34 (dd, J = 12.3 and 6.0 Hz, 1 H, 2‐H A benzothiazine), 3.43 (dt, J = 6.3 and 6.3 Hz, 2 H, 6‐H hexanoyl), 5.17 (qdd, J = 6.7, 6.0 and 4.6 Hz, 1 H, 3‐H benzothiazine), 5.23 (br.…”
Section: Methodsmentioning
confidence: 99%
“…Since the biological activity of chiral compounds is highly dependent on stereo configuration, we also synthesized and studied the individual enantiomers of the above derivatives. It should be noted that it has been recently shown that a modified riboside obtained from 2‐aminopurine conjugate with ( S )‐7,8‐difluoro‐3,4‐dihydro‐3‐methyl‐2 H ‐[1,4]benzoxazine attached directly at position 6 of purine core exhibits a high antiviral activity against HSV‐1; moreover, inhibitory activity of ( S )‐enantiomer was higher than that of ( R )‐enantiomer.…”
Section: Introductionmentioning
confidence: 99%